PENGARUH PEMBIAYAAN BERMASALAH TERHADAP PROFITABILITAS PADA PT. BANKSYARIAH INDONESIA KANTOR FUNGSIONAL OPERASIONAL (KFO) MIKRO PANDAN KOTA - Mardiah, Amii (Ekonomi : Jurnal Perbankan Syariah, 2024)
This research aims to determine whether there is a significant influence between problematic financing on profitability at PT. BankSyariah Indonesia KFO Micro Pandan City. The location of this research is PT. Bank Syariah Indonesia KFO Mikro Pandan Kota,and the population and sample are quarterly financial reports from January 2021- December 2022.The research method used in this research is quantitative research (correlation study), namely research based on data that can becalculated to produce an interpretation of how big the influence of problematic financing is on profitability. The data used is secondarydata, namely at https://ir.bankbsi.co.id/financial_reports.html. The data analysis technique used is simple linear regression analysis.This research found that the effect of problematic financing on profitability at PT. Bank Syariah Indonesia KFO Mikro Pandan Kotabased on the analysis is not significant as evidenced by the results of simple linear regression Y=776.695 – 2.197x where this figureshows a positive value indicating there is no significant influence between (0.086>0.05). This proves that problematic financing (x) isnot significant to profitability (y). Judging from the correlation test, the size of problematic financing on profitability is 4% andanother 96% is influenced by other factors that influence profitability at PT. Indonesian sharia bank KFO Mikro Pandan City.